Marketingový plán značky Rosteto - Komárek, Petr (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Tato diplomová práce se zaměřuje na problematiku marketingového plánování značky Rosteto. Autor analyzuje současný stav značky Rosteto a na základě jejíž výsledků a teoretického pozadí navrhuje specifické marketingové kroky k dosažení firmou stanovených cílů.

This master’s thesis focuses on the issue of marketing planning of Rosteto trademark. The author analyses current situation of the Rosteto and on the basis of the findings and theoretical background proposes the specific marketing activities in order to achieve the company’s goals.
Marketing Plan of Rosteto Trademark
Keywords: Marketing; marketingové plánování; marketingová strategie; marketingový mix; Rosteto; Marketing; marketing planning; marketing mix; Marketing strategy; Rosteto